Cerebellum and oxidative stress in natural and accelerated aging model - BAHAR, ASLI NUR (My University, 2023)
AIM: Intracerebroventricular administration of galactose causes motor coordination deficiency by decreasing glutathione (GSH) level in the cerebellum. It has been shown that aging increases oxidative stress and Sirtuin 2 (Sirt2) expression in rat cerebellum tissue and Sirt2 inhibition has a protective effect in aging. In our study, we aimed to investigate the effect of AGK-2 administration, a specific Sirt2 inhibitor, on oxidative stress in an accelerated aging model with natural and D-galactose (D-GAL) administration.METHODS: In the study, 7 groups were formed using 48 male rats of Wistar (W) and Sprague-Dawley (SD) species;1) Young-Control (3 months, n=6), 2) Young-AGK-2 (3 months, n=6), 3) Old-Control (22 months, n=6), 4) Old-AGK-2 (22 months, n=6), 5) D-GAL (3 months, n=9), 6) Solvent+D-GAL (3 months, n=8), 7) Solvent+D-GAL+AGK-2 (3 months, n=7). Control groups were given 4% DMSO+PBS, and experimental groups were given AGK-2 (10 μM/bw) subcutaneously (SC). For the accelerated aging model, D-galactose (150 mg/kg/day, SC) was administered for 10 weeks. Malondialdehyde (MDA) and GSH levels in cerebellum tissue were measured by spectrophotometric method.In the statistical analysis, one-way ANOVA (post-hoc LSD) was used to determine the differences between groups. The statistical significance level was set at p<0.05.RESULTS: The D-GAL administration increased the cerebellum MDA level significantly compared to the young control group (p<0.001). In the D-GAL group, AGK-2 administration decreased the MDA levels and increased the GSH levels (p=0.003; p=0.006). D-GAL administration increased MDA levels more and decreased GSH levels significantly compared to aged rats (p=0.006; p<0.001). AGK-2 administration in natural aging was found to be more effective in increasing GSH levels compared to the accelerated aging model (p<0.001).CONCLUSION: Both models compared increased oxidant stress in the cerebellum. AGK-2 application was found to be more effective than D-GAL on oxidant stress in natural aging.Keywords:AGK-2, Accelerated aging, Cerebellum, D-galactose, Natural aging, Oxidative Stress
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; AGK-2; Accelerated aging; Cerebellum; D-galactose; Natural aging; Oxidative Stress.